PROTOTYPE TEKNOLOGI SILUMAN (STEALTH) MATERIAL ORGANIK PENYERAP GELOMBANG RADAR DARI KOMPOSIT POLIMER CHITOSAN-HIDROKSIAPATIT UNTUK APLIKASI PERALATAN MILITER WILAYAH PERBATASAN - Fadhallah, Esa Ghanim; Firmanda, Elka; Hapsari, Nur Aziezah; Atmojo, Santoso Darmo; Irianto, Bayu (Program Kreativitas Mahasiswa - Penelitian, 2013)
Border regions in Indonesia are still often hit problems with other countries, and in other words it indicates weak military defense systems in the border area. Therefore, Indonesia needs to deploy some special forces on the frontier that uses advanced technology, one of them is the stealth technology. Radar absorbing material plays an important role in this technology. Chitosan and hydroxyapatite believed to resemble a good combination of new organic materials that can be developed as a radar absorbing material. The purpose of this study is to develop a prototype of organic radar absorbing material from chitosan-hydroxyapatite polymer composite. Quality characteristics of the material being analyzed are solution viscosity analysis, FTIR, SEM, material thickness, tensile strength. Ability of material to absorb radar waves was analyzed with reflection loss measurement. The prototype resembles a thin, transparent plastic sheet with a yellowish brown color. Values of thickness ranged from 0.14 to 0.17 mm. This material has a tensile strength values ranged from 1.41 ± 2.82 to 159.33 ± 106.33 kPa. SEM analysis showed a porous and homogeneous structure marked by good interaction between chitosan, PVA, and hydroxyapatite. Value of radar absorption by prototype shown with increasing the value of reflection loss. The optimum values obtained in the film with a mixture of chitosan prototype 2%, 5% PVA, and 0.04 gram hydroxyapatite with an average value of reflection loss -32.0907 ± 4.0763 dB.Keywords : chitosan, hydroxyapatite, polyvinyl alcohol, radar absorbing material, reflection loss